Energy harvesting communications : principles and theories - Chen, Yunfei, 1976- (John Wiley & Sons, Inc., 2019)
"A systematic overview of a hot research area, examining the state-of-the-art of energy harvesting techniques - Unique in providing a comprehensive coverage from basic energy harvesting sources and devices to energy end users. Also, it touches on the fundamental principles of energy harvesting wireless communications, and biomedical application and intra-body communications, allowing both beginners to learn this subject and experienced users to have a bigger picture - Follows a logical course from an introduction to energy sources and harvesters, then the limits of energy harvesting, including information theoretic limits as well as circuit implementation constraints, then the design of energy harvesting networks, where both physical layer issues and networking designs are covered, making it easy for practitioners to follow and to understand Market description: Primary: postgraduates,academic researchers, university faculty members, research associate/fellows, with backgrounds in the domain of wireless communications such as electronics/microwave engineering, information theory, game theory, control theory, and communication theory Secondary: reference book for professionals and practicing engineers"--